Navigating Technostressor: A Systematic Literature Review of Millennial Entrepreneurs - Khoirul Hikmah; Arief Subiyantoro; Marita Marita; Muhammad Ilham Fawwas; Aditya Wardana; Rifqi Syarif Nasrulloh (Research Synergy Foundation, 2026)
Millennial entrepreneurs' dependence on digital technology risks causing technostress, which can interfere with their mental health, productivity, and the quality of their business decisions. This study aims to identify, analyse, and synthesise the phenomenon of technostress among millennial entrepreneurs, focusing on the psychological, social, and individual performance impacts in the context of digital entrepreneurship. In an era of ever-evolving technology, technostress has become a major challenge for millennial entrepreneurs who are highly dependent on technology in running their businesses. This study uses the Systematic Literature Review (SLR) methodology by collecting Scopus-indexed articles published from 2023 to 2025 that are relevant to the topic of technostress among the millennial population. A total of 46 selected scopus articles were analysed using a thematic analysis approach to identify the causal factors, psychological impacts, and coping strategies used by millennial entrepreneurs. The results showed that technostress among millennial entrepreneurs is influenced by factors such as always-on technology, information overload, and the complexity of rapidly developing technology. The main psychological impacts that arise are anxiety, stress, digital fatigue, and decreased sleep quality, which affect well-being and business performance. However, coping strategies such as mindfulness, setting technology boundaries, and social support have been proven effective in reducing the impact of technostress. The novelty of this research lies in the development of propositions linking technostress to the dynamics of millennial entrepreneurship, as well as the importance of digital readiness and digital performance measurement in mitigating its negative impacts. The practical implications of this research suggest that millennial entrepreneurs implement holistic and personalised coping strategies and obtain relevant social support to maintain their well-being and business sustainability. This research also contributes theoretically by expanding the understanding of the relationship between technostress and digital entrepreneurship, as well as opening up directions for more comprehensive and contextual future research.